A simple method to calculate the degree of polymerization of alginate oligosaccharides and low molecular weight alginates. (1st December 2019) - Sun, Ming; Sun, Chu; Xie, Hongguo; Yan, Shenggang; Yin, Heng
Abstract: This study presents a quick, simple and accurate method to calculate the degree of polymerization (DP) of alginate oligosaccharides (AOS) and low molecular weight alginates from the concentration of reducing sugar determined by 3, 5-dinitrosalicylic acid (DNS) assay. 1 H NMR spectroscopy, mass spectroscopy (MS) and certified standards were used to verify the accuracy of this method, and the results showed DP calculated from DNS assay agreed with the actual DP. This method has great potential to simplify the process of measuring DP of alginate in lab and thus could be incorporated into various researches on alginates in the future. Moreover, similar method could be applied when studying the DP of other oligosaccharides. Graphical abstract: A quick, simple and accurate method to calculate the degree of polymerization (DP) of alginate oligosaccharides (AOS) and low molecular weight alginate just from the concentration of reducing sugar determined by 3, 5-dinitrosalicylic acid (DNS) assay. Image 1 Highlights: A quick, simple and accurate method to calculate the degree of polymerization. A linear relationship between the concentration of reducing sugar in water and DP. Similar method could be used in researches on other oligosaccharides.